ANALISIS PENURUNAN CACAT PINHOLE PADA PRODUK BREATHABLE BACKSHEET FILM DENGAN METODE DMAIC DAN SIX SIGMA - Zacky Fahd Mustafa; Oleh ,; Iwan Gusniar (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to reduce pinhole defects that cause the rejects on breathable backsheet film products with the six sigma method approach through the tool, namely DMAIC. The define phase will define any problems that cause product rejection, then in the measure phase the sigma value calculation is carried out from the production process, then in the analyze phase an analysis of the pinhole causes is carried out, then in the improve phase improvements are made to the pinhole causes, lastly on the control phase is carried out by comparing the data from the measure stage before and after the repair. From the analysis, it can be concluded that the main cause of pinhole is the presence of dust in the recycle material. Improvements were made by making a dust separator for recycled materials and providing training to operators. The result of the improvement is a decrease in the number of pinholes and an increase in the sigma number of the process.